Iraq : 2007 Article IV Consultation, Fifth Review Under the Stand-By Arrangement, Financing Assurances Review, and Requests for Extension of the Arrangement, Waiver of Applicability, and Waivers for Nonobservance of Performance Criteria; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Iraq. (IMF Staff Country Reports; Country Report, 2007)
This 2007 Article IV Consultation highlights that Iraq's economic growth has been slower than expected at the time of the last Article IV Consultation, mainly because the expected expansion of oil production has not materialized. Following a decline in oil production and real GDP in 2005, economic growth is estimated at 6u percent in 2006. Progress in implementing the structural reforms has been made. Official fuel prices have been increased to levels in other oil-exporting countries in the region, and private sector importation of fuel products has been liberalized.